A COMPARATIVE STUDY OF THE DYNAMICS OF LABORATORY STRAINS INFECTIVITY AND COXSACKIE B VIRAL CLINICAL ISOLATES - V.A. Poniatowsky; V.V. Bobyr; V.B. Nastenko (Bogomolets National Medical University, 2016)
The problem of enteroviruses survival has the great importance when correct estimate forms about the danger of the viral infections epidemic spread. The particular relevance of this problem associated with biological characteristics of viruses, which are only present in the environment, but do not multiply in it. The purpose of this study is comparative analysis of conservation of infectivity Coxsackie B clinical isolates and laboratory strains in vitro. Museum prototypic strains and clinical isolates of virus Coxsackie B and Coxsackie B6 have been used in studies. Molecular genetic methods, namely PCR, were used to verification of the presence of virus in clinical samples. The experimental results indicate about high stability comparatively of studied viral populations at 4oC. The sharp decline of enteroviruses resistance during temperature increases. At 200C most of the samples inactivated to 60 days of research. Although it should be noted than clinical isolates demonstrated more stability at 200C: its kept infectivity to 60 days of research in titer 1,0lg10. Dynamics of clinical and prototypical strains of Coxsackie B3 and Coxsackie B6 inactivation was almost the same: already at 36 storage hours viral infectious agents were not detected in prototypes. Higher resistance of Coxsackie B clinical isolates has been noted compared with museum prototypical strains of these microorganisms. Besides, results of research point the decline of Coxsackie B clinical isolates resistance after prolonged cultivation in cell cuiture. Coxsackie B clinical isolates resistance does not differ from laboratory strains resistance of these microorganisms after six passages.